EFEKTIVITAS PELATIHAN DALAM MENDORONG TRANSISI USIA MUDA KE PASAR TENAGA KERJA: SYSTEMATIC LITERATURE REVIEW - Denok Ambun Suri; Herni Pujiati (SINERGI : Jurnal Riset Ilmiah, 2026)
Youth unemployment remains a major labour market issue, closely related to the transition from education or non-employment into work. Job training is often positioned as an instrument to improve young people’s work readiness and competitiveness; however, previous studies suggest that its effects on employment outcomes are not always direct or consistent. This study aims to synthesize the existing literature on the effectiveness of training in supporting young people’s transition into the labour market. Using a systematic literature review approach guided by the PRISMA 2020 framework, this study analysed English-language journal articles indexed in Scopus and published between 2016 and 2026. The initial search identified 241 articles, of which 1 duplicate was removed, leaving 240 articles for title and abstract screening. Of these, 54 articles were excluded and 186 articles were retained for eligibility assessment. The initial mapping shows that the literature mainly discusses vocational training, TVET, employability, school-to-work transition, work experience, certification, skills mismatch, digital literacy, and vulnerable groups. The findings indicate that training should not be understood as a stand-alone intervention, as its contribution to young people’s labour market transition depends on practical experience, certification, soft skills, digital literacy, labour market information, job matching, and linkages with employers. This study concludes that the effectiveness of training in accelerating youth labour market transition is shaped by programme design quality and the broader support ecosystem surrounding the training.